Effect of Gamma Radiation on Creep Behavior, Hardness and Microstructure of Titanium Dental Material - Bediwi, A. El; Kashita, Eman; M .M.Salman, Salah. (JOURNAL OF ADVANCES IN PHYSICS, 2017)
Effect of gamma radiation with fixed doses on creep behavior, Vickers hardness, maximum shear stress and surface roughness parameters of cp Titanium have been investigated. Vickers hardness and maximum shear stress values of cp Titanium are decreased after irradiated at 10, 20 and 30 kGy. Surface roughness Ra of cp Titanium varied after irradiated at 10, 20 and 30 kGy. Stress exponent values of cp Titanium decreased after irradiated at 10, 20 and 30 kGy. Matrix microstructure of cp Titanium changed (Intensity, broadness and position) after irradiated at 10, 20 and 30 kGy.